2006
DOI: 10.1111/j.1875-595x.2006.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic restorative treatment (ART): the Tanzanian experience

Abstract: An increased involvement and support for ART from the Ministry of Health and professional organisations, and public education of ART is called for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
12
0
2
Order By: Relevance
“…A survey on perceived oral health care needs in a low‐income country revealed that perceived oral health problems were strongly related to pain and discomfort (166). In line with this perception is the relief of pain because of the sequela of dental caries as the main reason for people to visit a dental clinic in low‐income countries such as Sri Lanka (167, 168), Tanzania (169, 170), Cambodia (171), China (172), Vietnam (173), Nigeria (174) and Burkina Faso (175).…”
Section: Quo Vadis? Priorities In Oral Health Care For Low‐ and Middlmentioning
confidence: 99%
“…A survey on perceived oral health care needs in a low‐income country revealed that perceived oral health problems were strongly related to pain and discomfort (166). In line with this perception is the relief of pain because of the sequela of dental caries as the main reason for people to visit a dental clinic in low‐income countries such as Sri Lanka (167, 168), Tanzania (169, 170), Cambodia (171), China (172), Vietnam (173), Nigeria (174) and Burkina Faso (175).…”
Section: Quo Vadis? Priorities In Oral Health Care For Low‐ and Middlmentioning
confidence: 99%
“…It is inevitable that one reason is that some dentists have neither heard of ART nor practiced it 7 , or are not trained and do not feel competent to practice it 41 . However, for those who are cognisant of the approach, it would be useful to identify whether the barriers to using ART are economic, relate to social and peer norms or relate to ingrained beliefs that ART is a substandard and temporary treatment, to be considered only for the poor and disadvantaged.…”
Section: Community Public Health and Health Services Researchmentioning
confidence: 99%
“…The atraumatic restorative treatment (ART), an MCP technique, employs hand instruments in the cavity preparation and an adhesive restorative material like glass ionomer cement (GIC) 3 . As the ART technique can be applied without the need for sophisticated equipment, running water or electricity, it offers the opportunity for restorative work in children from poor communities 4 .…”
Section: Introductionmentioning
confidence: 99%